Pengaruh Servant Leadership terhadap Kinerja Karyawan dengan Burnout sebagai Variabel Intervening - Aji, Muhammad; Palupiningdyah, Palupiningdyah (Management Analysis Journal, 2016)
Human resource issues becomes the significant challenge for the company management. A new approach in leadership could simultaneously increase the employees personal growth and repair the quality and services. An effort to achieve that condition at the workplace is necessary to be applied by a leadership model known as servant leadership. This study aims to investigate the influence of self-leadership to the employee performance with bornout as the intervening variable on the employees of PT. Inti Roda Makmur Persada Tbk Tangerang. The population of this study is all the employees of PT. Inti Roda Makmur Persada Tbk Tangerang. Sampling technique using proportionate random sampling, there are 64 respondents. The methods of collecting the data are observation, questionnaires and literature. Data analysis using linear regression and line analysis. The result showed that t value is proved that servant leadership contributes positive and significant impact on the burnout. The second research results obtained proven that servant leadership gives positive influence and significant impact on the performance directly. The third result showed that burnout give negative effect And significant on the performance directly.  And the next result showed that servant leadership to performance by burnout give negative affect and significant.